Modification Effect of Cellulase on the Physicochemical Characteristic of Polysaccharides Edible Films. (16th August 2015) - Zimoch-Korzycka, Anna; Ambrozik-Haba, Jagoda; Kulig, Dominika; Jarmoluk, Andrzej
Abstract : This study was conducted to assess hydrolytic influence of cellulase (C) on the physicochemical stability of chitosan (CH)/hydroxypropyl methylcellulose (HPMC) films in time of storage ( T ). Initially, nine films were physically characterized by contact angle, water vapour permeability (WVP), water activity( a w ), tensile test, dynamic mechanical thermal analysis (DMTA), and thermogravimetric analysis (TGA) and chemically by Fourier Transform Infrared Spectrometry (FTIR). The contact angle results varied from 53.67° to 78.33°. The presence of the enzyme and passing time reduced the WVP from8.46 E - 09 to7.41 E - 09  g/s·m·Pa. The enzyme treatment improved elasticity but decreased tensile strength of films. After adding cellulaseT g was shifted to a higher temperature. Thermal stability of the films decreased with addition of cellulase and after prolonging storage time. FTIR analysis proved that chemical changes in polysaccharides structure were caused by cellulase incorporation in films composition, which may be observed in appearance of 1656 cm −1 band. Thea w values did not change.